Needs Analysis for Genially-Assisted Project-Based Student Worksheets in Light Vehicle Engineering Vocational Schools - A Mirza Mutazza; Taufiqulloh Taufiqulloh; Dewi Amaliah Nafiati (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study aims to analyze the need for the development of Genially-assisted project-based Student Worksheets for Light Vehicle Engineering subjects at Vocational High Schools in Tegal Regency. The study used a quantitative descriptive approach involving 8 teachers and 24 grade XI students from eight Vocational High Schools with Light Vehicle Engineering expertise. Data were collected through expert-validated needs questionnaires and analyzed using quantitative descriptive techniques in the form of averages and categories of needs. The results showed that teachers' needs for the development of Genially-assisted project-based Student Worksheets obtained an average score of 3.82 on a scale of 4.00 with a very high category, while students' needs obtained an average score of 3.79 with a very high category. Teachers assessed that learning was still dominated by lecture methods and needed interactive digital teaching materials to increase student engagement and support project-based learning. Meanwhile, students showed a high need for learning media containing videos, animations, interactive quizzes, and flexible access through digital devices to help understand the drum brake system material. These findings indicate that Genially's project-based student worksheet development has the potential to be an innovative solution to support more active, contextual, and interactive vocational learning, while also supporting student independence. This research is limited to analyzing the needs of Tegal Regency, so further research is needed to test the effectiveness of the developed student worksheet in a broader context and sample.